PROFESSIONAL IMAM AND KHATIB TRAINING TO IMPROVE THE QUALITY OF WORSHIP AND DELIVERY AT MA KHAIRUL UMMAH - Taufik Hidayat (RADJA PUBLIKA, 2026)
Professional training for imams and khatibs is a strategic initiative aimed at improving the quality of religious services and the effectiveness of da'wah within educational settings. This initiative is driven by the critical role that imams and khatibs play as central figures in guiding the community, particularly within the Khairul Ummah Madrasah Aliyah (MA). The objective of this training is to enhance participants' competencies in Quranic recitation, understanding of worship jurisprudence (fiqh), da'wah rhetoric, and self-confidence in delivering communicative and inspirational sermons. The training methods include lectures, hands-on practice, sermon simulations, and continuous evaluation. The training participants are selected students with potential in religious fields. The results of this activity demonstrate an improvement in the participants' ability to lead prayers with proper recitation and accuracy, as well as to deliver sermons with a systematic structure, clear language, and messages relevant to the congregation's needs. Thus, the professional imam and khatib training at MA Khairul Ummah makes a positive contribution to shaping a young generation that is competent in religious matters and capable of becoming effective agents of da'wah in the community. It is hoped that this activity will continue and become a flagship program in the development of students' religious character.